Penerapan Good Governance Dalam Pengelolaan Dana Desa di Desa Tukamasea Kecamatan Bantimurung Kabupaten Maros - Amelia Callista Putri Iskhas; Hariany Idris; Samsinar (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of good governance in the management of village funds in Tukamasea Village, Bantimurung District, Maros Regency. The research variable is the Implementation of Good Governance in Village Fund Management as (X1) by analyzing accountability, transparency, and participation in the management of village funds in Tukamasea Village based on the Regulation of the Minister of Home Affairs Number 20 of 2018. The subjects of this study were all village officials involved in the management of village funds. The data collection techniques used were interviews and documentation. The data analysis used Qualitative Descriptive Analysis. The results of this study indicate that Tukamasea Village has implemented the principles of Good Governance in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018, especially on the principles of Transparency and Participation. However, Tukamasea Village has not implemented the principle of accountability 100%. This is because there is no documentary evidence that the village has reported to the Sub-district Head and the Regent of Maros.